The low FODMAP diet for IBS; A multicentre UK study assessing long term follow up. Issue 11 (November 2021) - Rej, Anupam; Shaw, Christian C.; Buckle, Rachel L.; Trott, Nick; Agrawal, Anurag; Mosey, Karen; Sanders, Katie; Allen, Rupert; Martin, Sophie; Newton, Aimee; Robinson, Kelly; Elphick, David; et al.
Abstract: Background: The low FODMAP diet (LFD) is effective in managing irritable bowel syndrome (IBS) in the short term. This study assessed the long-term effect of the LFD on symptoms, nutritional composition and socialising. Methods: Patients with IBS who received dietetic-led LFD advice were approached at long term follow up (>6 months post LFD advice) from six centres across the United Kingdom. Participants completed questionnaires assessing gastrointestinal symptoms, adherence, nutritional intake, dietary acceptability and food related quality of life (QOL). Results: 205 participants completed the study, with a mean follow up of 44 months (3.7 years). Adequate symptom relief was noted in 60% of individuals at long term follow up, with 76% being on the personalisation phase of the LFD (pLFD). Mean nutritional intake did not differ between individuals on the pLFD versus habitual diet, with no difference in fructan intake (2.9 g/d vs 2.9 g/d, p = 0.96). The majority (80%) of individuals on the pLFD consumed specific 'free-from' products at the long term, with the purchase of gluten or wheat free products being the commonest (68%). Conclusion: The majority of patients follow the pLFD in the long term, with a large proportion purchasing gluten or wheat free products to manage their symptoms.